Propagation of Type III Bursts Emission in the Solar Corona. II. Frequency Drift Rate - Rutkevych, B. P.; Melnik, V. M. (Видавничий дім «Академперіодика», 2012)
In this paper we consider electromagnetic waves that are gene- rated by a beam of fast electrons in the variable density plasma of the solar corona, and analyze the influence of the propagation effects on the frequency drift rate of the type III bursts. An analytical expression for the drift rate for two models of the corona density are obtained in the limit of small-size electron beam. For a finite sized beam, the frequency drift rate is determined numerically for the observed values of the electron beam velocity vector, and we show that the decameter type III bursts and fast type III bursts can be explained within a unified model. Variation of the drift rate versus frequency is derived numeri- cally for an expanding beam. Approximation of the numerical drift rate profile is in good agreement with the empirical dependence obtained by Alvarez and Haddock (1973) based on observational data.